2022
DOI: 10.3389/fonc.2022.841980
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of MRI-Guided Adaptive Brachytherapy for Each Fraction in Locally Advanced Cervical Cancer: A Single Institution Experience

Abstract: PurposeThis study aims to evaluate clinical outcomes of MRI-guided adaptive brachytherapy (MR-IGABT) for each brachytherapy fraction in patients with locally advanced cervical cancer (LACC).Methods and MaterialsA retrospective analysis was performed on 97 consecutive patients with LACC treated with 44.0–50.4 Gy external beam radiotherapy (EBRT) ± concurrent platinum-containing chemotherapy followed by 4 × 7 Gy MR-IGABT between September 2014 and April 2019. Intracavitary (IC)/interstitial (IS)/hybrid intracavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
0
1
Order By: Relevance
“…They reported that the 2-year OS was 83.5% and the 2-year LC was 94.8%. Their 2-year LC was higher than ours, which was possibly caused by the proportion of patients with advanced cervical cancer staging was relatively higher in our study [11].…”
Section: Discussioncontrasting
confidence: 78%
“…They reported that the 2-year OS was 83.5% and the 2-year LC was 94.8%. Their 2-year LC was higher than ours, which was possibly caused by the proportion of patients with advanced cervical cancer staging was relatively higher in our study [11].…”
Section: Discussioncontrasting
confidence: 78%